Pembelajaran Sila dan Meditasi Cinta Kasih Terhadap Perubahan Perilaku Adaptif siswa-siswa SDN 2 Mareje - Mayani Mayani; Partono Nyanasuryanadi; Budi Utomo (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2026)
The purpose of this study is to examine the influence of Sila learning (X₁) and loving-kindness meditation (X₂) on adaptive behavior among 85 students at SDN 2 Mareje. Data collection techniques consisted of questionnaires and observations, while data analysis techniques included classical assumption tests, multiple linear regression, t-tests, F-tests, and the coefficient of determination. The results of multiple linear regression analysis showed that the coefficient of determination (R Square) was 0.779, indicating that 77.9% of the variability in students’ adaptive behavior was explained simultaneously by Sila learning and loving-kindness meditation, while the remaining 22.1% was influenced by other factors outside the research model. The multiple correlation coefficient (R) of 0.738 indicates a strong and positive relationship between the combination of the two independent variables and students’ adaptive behavior.